Transforming Cambodian Education: Full-Time Learning, Technology, and Language Integration for Public Schools - Thuon, Nimol; Theang, Panhapin (MASI Mandiri Edukasi, 2024)
The Cambodian government has announced a significant educational reform to transition public schools to full-time learning by integrating computer and English or Chinese language classes. This initiative is designed to enhance the quality of education and better prepare students for the demands of the modern world. This paper compares these proposed changes by examining practices in five private schools already implementing full-time education and advanced technological and multilingual programs. By evaluating the academic performance, resource availability, and overall educational outcomes of these private schools, this study aims to provide actionable recommendations for successfully adopting these strategies in public schools. The research involved surveys of 565 respondents, including students, teachers, school administrators, parents, and policymakers, and in-depth interviews with 50 key stakeholders. Key findings include strong support for full-time education, higher levels of technology integration, and better multilingual education in private schools. These findings will inform policymakers, educators, and stakeholders about the potential impacts and necessary steps to ensure the successful implementation of these educational reforms in Cambodia's public school system.